2014
DOI: 10.1111/jabr.12026
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Minimally Important Differences (MIDs) for Two Patient‐Reported Outcomes Measurement Information System (PROMIS) Computer‐Adaptive Tests in Chronic Pain Patients

Abstract: Anchor-and distribution-based methods were combined to evaluate and establish minimally important differences (MIDs) for two Patient-Reported Outcomes Measurement Information System (PROMIS) measures in an outpatient chronic pain population. These included the computer-adaptive test (CAT) versions of two PROMIS measures: Depressive Symptoms and Anxiety-Related Symptoms (PROMIS; Cella, Gershon, Lai & Choi). Participants (n = 170) undergoing a behavioral medicine evaluation in an interdisciplinary pain managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“… 38 For depression, the noninferiority margin was 4 points on the PROMIS depression measure, which is defined as the minimally important difference and represents a Cohen d effect size of approximately 0.50. 39 , 40 , 41 The proportion with clinically meaningful improvement or worsening of depressive symptoms was assessed using stringent (≥8 points) and less stringent (≥4 points) criteria.…”
Section: Methodsmentioning
confidence: 99%
“… 38 For depression, the noninferiority margin was 4 points on the PROMIS depression measure, which is defined as the minimally important difference and represents a Cohen d effect size of approximately 0.50. 39 , 40 , 41 The proportion with clinically meaningful improvement or worsening of depressive symptoms was assessed using stringent (≥8 points) and less stringent (≥4 points) criteria.…”
Section: Methodsmentioning
confidence: 99%
“…11 On the basis of prior PROMIS validation studies in cancer, we considered a group score difference of 3 points likely to be clinically meaningful. 12,13 Published symptom cutoff scores for pain interference, fatigue, anxiety, and depression were used to describe symptom severity (none, mild, moderate, or severe). 14…”
Section: Promis Measuresmentioning
confidence: 99%
“…23 However, further observational and clinical research has shown minimally important difference (MID) to be much lower, near 3.5. 40,41 In fact, a recent randomized trial showed a MID of 3.0 along the PROMIS depression domain. 42 Our detected change of 4.5 likely conveys a meaningful change.…”
Section: Discussionmentioning
confidence: 99%
“…Initial theory suggested that half of a SD, a t ‐score change of 5 points, is considered clinically meaningful 23 . However, further observational and clinical research has shown minimally important difference (MID) to be much lower, near 3.5 40,41 . In fact, a recent randomized trial showed a MID of 3.0 along the PROMIS depression domain 42 .…”
Section: Discussionmentioning
confidence: 99%